2008
DOI: 10.1159/000128575
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Adapted Whole-Blood Interferon-γ Release Assays for the Diagnosis of Pleural Tuberculosis

Abstract: Background: Pleural tuberculosis (TB) remains difficult to diagnose despite numerous diagnostic tools. Recently, in vitro interferon (IFN)-γ-based assays have been introduced in the diagnosis of latent TB, but these techniques have not been established in the diagnosis of active TB disease, including pleural TB. Objectives: It was the aim of this study to assess the accuracy of the commercially available QuantiFERON® TB Gold assay and adapted variants of the assay, using pleural fluid or isolated pleural fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
83
1
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 49 publications
1
83
1
3
Order By: Relevance
“…A recent meta-analysis of 7 studies that included 213 patients with TB pleural effusions found the sensitivity and specificity of IGRA measurements in pleural fluid to be 0.75 and 0.82, respectively [51]. Moreover, another study showed that measuring γ-interferon levels in pleural fluid was superior to IGRA in regards to both sensitivity and specificity [52]. Using IGRAs for blood or pleural fluid is not recommended for making a diagnosis of TB pleuritis [53].…”
Section: Interferon-gammamentioning
confidence: 99%
“…A recent meta-analysis of 7 studies that included 213 patients with TB pleural effusions found the sensitivity and specificity of IGRA measurements in pleural fluid to be 0.75 and 0.82, respectively [51]. Moreover, another study showed that measuring γ-interferon levels in pleural fluid was superior to IGRA in regards to both sensitivity and specificity [52]. Using IGRAs for blood or pleural fluid is not recommended for making a diagnosis of TB pleuritis [53].…”
Section: Interferon-gammamentioning
confidence: 99%
“…In the last several months, two case-control studies from high-burden countries (South Africa) and using QFT-TB-GIT have been published [15,16]. Both showed that the QFT-TB-GIT assay had suboptimal sensitivity (27 and 57%, respectively).…”
Section: Pleural Hbha and Ppd Elispot Responsesmentioning
confidence: 99%
“…We therefore hypothesised that TB antigen-specific responses could distinguish active pleural TB from alternative diagnoses and should have better discriminatory value than unstimulated IFN-c, a nonspecific biomarker of inflammation. A recent case-control study from Europe showed a high diagnostic accuracy with the T-SPOT.1TB assay (Oxford Immunotec, Abingdon, UK) [13] but overall data on the utility of two known IFN-c release assays (IGRAs), T-SPOT.1TB and QuantiFERON1-TB Gold In-tube (QFT-TB-GIT; Cellestis, Carnegie, Australia), including a head-to-head comparison, for the diagnosis of TB-PE are limited [13][14][15][16]. There are several other unresolved questions, including the optimal cell number and pleural fluid volume required, optimal cut-off point and utility in high HIV-prevalence settings [17].…”
mentioning
confidence: 99%
“…To date, Chegou and co-workers have shown that ex vivo pleural fluid IFN-y levels accurately identified TB in all patients in a high burden area, suggesting IGRA to have a poor additional diagnostic value (20). Detection of whole IFN-y was superior to QFT-IT using blood and pleural fluid (73% and 57% sensitivity, with 71% and 87% specificity, respectively) and to QFT-G (the predecessor of QFT-IT) applied to isolated pleural fluid cells (100% sensitivity and 67% specificity).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the fact that IGRA do not discriminate LTBI from active TB, pooled sensitivity of blood assays has recently been estimated to be higher than 80% in detecting active TB disease as a surrogate of TB infection, at least in developed countries (11)(12). Some reports indicate that IGRAs might be helpful in selected cases of pulmonary TB cases (13)(14)(15)(16)(17) and in patients with extra-pulmonary TB, including plTB and TB meningitis, by detecting the release of IFN-y by antigen-specific T cells directly at the infection site (18)(19)(20)(21)(22)(23)(24)(25).…”
mentioning
confidence: 99%